Gas outflow in Seyfert galaxies: 3D radiative cooling hydrodynamical simulations. Issue Volume 10:Issue S313(2014) (24th March 2015) - Melioli, Claudio; de Gouveia Dal Pino, Elisabete M.
Abstract: Accreting supermassive black holes and starburst regions influence their host galaxies through kinetic/radiative feedback processes. To better understand the gas evolution of a Seyfert galaxy, in this study we perform fully 3D hydrodynamical simulations with radiative cooling considering the presence of star formation regions, supernova feedback and small-scale (1 kpc) jet propagation in the central region of an active spiral galaxy. We compute the gas mass lost by the system and we conclude that a kpc-scale outflow is generally established only when a nuclear starburst region is coupled to a supermassive black hole jet.